Wiley Encyclopedia of Chemical Biology 2008
DOI: 10.1002/9780470048672.wecb328
|View full text |Cite
|
Sign up to set email alerts
|

Metallointercalators as Probes of DNA Recognition and Reactions

Abstract: Here we describe studies of metallointercalators bound to DNA. These octahedral transition metal complexes primarily bind noncovalently by stacking within the DNA helix. Given the rich photophysics and photochemistry of the ruthenium and rhodium complexes we employ, we have used a variety of biophysical studies to characterize their interactions with DNA. X‐ray crystallography has also provided atomic resolution detail as to their binding to the duplex. Complexes have been designed that target DNA with high sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…(18, 33) This low reduction potential means that RPCs are readily reduced by common cellular reductants, and we have shown that these reductions are centered on the tatpp ligand, not the Ru(II) ion, with concomitant formation of a carbon radical species. Because RPCs 3 2+ and 4 4+ as well as related complexes 2 4+ , [Ru(phen) 2 (dppz)] 2+ , and [Ru(phen) 2 (tpphz)] 2+ , are known to bind DNA via intercalation,(18) the tatpp carbon radical in the reduced species is in intimate contact with the DNA. We hypothesize that H atom abstraction from the deoxyribose unit as the likely mechanism of DNA damage.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…(18, 33) This low reduction potential means that RPCs are readily reduced by common cellular reductants, and we have shown that these reductions are centered on the tatpp ligand, not the Ru(II) ion, with concomitant formation of a carbon radical species. Because RPCs 3 2+ and 4 4+ as well as related complexes 2 4+ , [Ru(phen) 2 (dppz)] 2+ , and [Ru(phen) 2 (tpphz)] 2+ , are known to bind DNA via intercalation,(18) the tatpp carbon radical in the reduced species is in intimate contact with the DNA. We hypothesize that H atom abstraction from the deoxyribose unit as the likely mechanism of DNA damage.…”
Section: Discussionmentioning
confidence: 91%
“…These findings concur with the known subcellular localization of these compounds in the nucleus and mitochondria, and with previous studies of RPC 3 2+ and 4 4+ that binds DNA tightly (K b ~ 10 8 M −1 , in vitro ) via an intercalative mode, (45, 46) typical for RPCs with large planar aromatic rings. (18) Indeed, analysis of the whole cell (wc) and nuclear fractions (nf) of RPC treated (5 µM) H-358 cells for uptake of ruthenium by graphite furnace atomic absorption spectroscopy, a showed early concentration spikes in the nf. After 1 h incubation, cells revealed [Ru] of ~7 µg RPC/mg wc and ~27 µg RPC/mg nf for both Δ- 3 2+ and ΔΔ- 4 4+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Design of luminescent metal complexes capable of intercalating between DNA base pairs is an extensively investigated topic. , Specific interaction of metal complexes with DNA strands, coupled with modification of luminescence outputs, allows such systems to efficiently perform the function of probes of DNA sites. Moreover, beside the probing function, interaction of photoactive metal complexes with DNA can also yield information on the DNA electron/hole transport ability, , obtain photoreactions involving DNA sites, leading to specific DNA damage, , and assemble elaborate, interesting supramolecular architectures …”
mentioning
confidence: 99%
“…More recently, the DNA-binding and molecular-light switch behavior of [Ru(phen) 2 (dppz)] 2+ ( 6 2+ ) 37 and [Ru(phen) 2 (tpphz)] 2+ ( 7 2+ ) 38 , 39 has led to a resurgence in this area, with numerous studies of their uses as biological probes 40 45 and the inherent (non-light activated) cytotoxicity of RPCs. 34 , 39 , 43 , 46 54 Because of the tendency of RPCs to bind DNA, it is often assumed that this is the biological target, 55 58 although recent data reveal that other cellular organelles are sometimes targeted, including the mitochondria, 46 , 52 , 54 , 59 64 endoplasmic reticulum, 42 ribosomes 65 and cell membrane.…”
Section: Introductionmentioning
confidence: 99%